Acute effects of exercise with blood flow restriction on endothelial function in healthy young and older populations: a systematic review - Gustavo Gonçalves Cardozo; Karynne Grutter Lopes; Daniel Alexandre Bottino; Maria das Graças Coelho de Souza; Eliete Bouskela; Paulo Farinatti; Ricardo Brandão de Oliveira (Brazilian Society of Geriatrics and Gerontology, 2023)
The objective of this review is to identify the acute effects of blood flow restriction (BFR) with vs without exercise on endothelial function in healthy individuals and the changes in endothelial function in young and older adults following different levels of exclusive BFR vs free flow. Systematic searches were performed in the following databases: PubMed, Web of Science, Scopus, and Cochrane Library, from inception to July 17, 2021. The studies included healthy individuals who underwent assessments of endothelial function before and after experimental protocols through endothelium-dependent flow-mediated dilatation. In total, 4890 studies were screened, and 6 studies of moderate-to-high methodological quality (Physiotherapy Evidence Database scores 6 - 10) including 82 subjects (aged 24 - 68 years) were eligible. Overall, flow-mediated dilatation increased in the non-cuffed arm immediately and 15 minutes after exercise, with no change in the cuffed arm (BFR of 60 - 80 mmHg). In protocols without exercise, cuff pressures of 25 - 30 mmHg applied for 30 minutes did not promote changes in the endothelial function, while those > 50 mmHg induced a dose-dependent attenuation of flow-mediated dilatation only in young individuals. A moderate level of BFR appears to have no effect on endothelial function after acute exercise. In non-exercise conditions, reductions in flow-mediated dilatation seem to result from increased retrograde shear provoked by cuff pressures ≥ 50 mmHg in young but not in older adults. An exercise-related increase in antegrade shear rate leads to a greater nitric oxide-mediated vasodilator response. However, BFR appears to attenuate this effect in young but not in older individuals.